2011
DOI: 10.1002/jez.b.21439
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of duplicate γ‐glutamyl transferase genes in teleosts: medaka (Oryzias latipes), stickleback (Gasterosteus aculeatus), green spotted pufferfish (Tetraodon nigroviridis), fugu (Takifugu rubripes), and zebrafish (Danio rerio)

Abstract: The availability of multiple teleost (bony fish) genomes is providing unprecedented opportunities to understand the diversity and function of gene duplication events using comparative genomics. Here we examine multiple paralogous genes of γ-glutamyl transferase (GGT) in several distantly related teleost species including medaka, stickleback, green spotted pufferfish, fugu and zebrafish. Through mining genome databases, we have identified multiple GGT orthologs. Duplicate (paralogous) GGT sequences for GGT1 (GG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Information on the expression of GGT5 in other vertebrates is derived primarily from mRNA studies in mice, rats and fish (Carter et al 1998; Potdar et al 1997; Law et al 2012). The most striking difference in GGT5 expression between mouse and human tissues was that in the mouse, macrophages lacked GGT5 expression, while in humans GGT5-positive macrophages were observed in many tissues (Carter et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Information on the expression of GGT5 in other vertebrates is derived primarily from mRNA studies in mice, rats and fish (Carter et al 1998; Potdar et al 1997; Law et al 2012). The most striking difference in GGT5 expression between mouse and human tissues was that in the mouse, macrophages lacked GGT5 expression, while in humans GGT5-positive macrophages were observed in many tissues (Carter et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…GGT1 is present in bacteria and throughout the plant and animal kingdoms while GGT5 is present only in vertebrates (Law et al 2012; Okada et al 2006; Bello and Epstein 2013). Phylogenetic analyses indicate that GGT5 arose from a duplication of the GGT1 gene in the vertebrate lineage after divergence from Branchiostoma but before the divergence of amphibians and teleost fish (Law et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, a number of carriers, such as members of the oatp/OATP superfamily, help to transport MC-RR-GSH to the kidney and/or help to transport MC-RR-Cys produced by other organs, such as the liver, into the kidney (Fischer et al, 2005;Hagenbuch and Meier, 2003;Lohr et al, 1998;Meier et al, 1997;Meier and Stieger, 2002). Additionally, the MC-RR-GSH arriving in the kidney was rapidly and effectively converted to MC-RR-Cys, as high gamma-glutamyltranspeptidase (GGT) and cysteinylglycine dipeptidase activities, which catalyze this conversion process, were found in the kidneys of mammals and fish (Elfarra and Anders, 1984;Hughey et al, 1978;Kera et al, 1999;Law et al, 2012). Previous studies observed significant induction of GGT genes in medaka larvae within 15 min after treatment with tert-butyl hydroquinone (tBHQ) in the rearing solution (Law et al, 2012).…”
Section: Mc-gsh and Mc-cys Have Been Identified As Two Importantmentioning
confidence: 99%
“…Additionally, the MC-RR-GSH arriving in the kidney was rapidly and effectively converted to MC-RR-Cys, as high gamma-glutamyltranspeptidase (GGT) and cysteinylglycine dipeptidase activities, which catalyze this conversion process, were found in the kidneys of mammals and fish (Elfarra and Anders, 1984;Hughey et al, 1978;Kera et al, 1999;Law et al, 2012). Previous studies observed significant induction of GGT genes in medaka larvae within 15 min after treatment with tert-butyl hydroquinone (tBHQ) in the rearing solution (Law et al, 2012). Based on these related research data together with the present results, we infer that the renal metabolism may play a major role in the processing of MC-RR-GSH into MC-RR-Cys in fish like bighead carp, as well as in the accumulation of MC-RR-Cys in the kidney for excretion.…”
Section: Mc-gsh and Mc-cys Have Been Identified As Two Importantmentioning
confidence: 99%